Lightweight high-strength high-toughness green concrete and preparation method thereof

By using a combination of geological polymers, hollow microbeads and chopped fibers, the problem of insufficient performance of traditional concrete materials is solved, and lightweight, high-strength and high-toughness green concrete is prepared, achieving the dual advantages of low carbon and environmental protection and high performance.

CN119462035APending Publication Date: 2025-02-18GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311007811.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional concrete materials have problems such as heavy self-weight, low strength, poor toughness, insufficient durability and serious environmental pollution, which are difficult to meet the needs of modern buildings for high-performance concrete.

Method used

Geological polymers are used as gelling material, hollow microbeads are combined as lightweight aggregate, and chopped fibers are added to improve toughness to prepare lightweight, high-strength and high-toughness green concrete.

Benefits of technology

It has achieved low-carbon and environmentally friendly concrete materials, with a density reduced to 54-75% ordinary concrete, a compressive strength of 40-90MPa, a strain rate of up to 8.3%, and significantly improved the durability and tensile properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete materials, and relates to lightweight high-strength high-toughness green concrete and a preparation method thereof. The brick is prepared from the following raw materials in parts by weight: 21-30 parts of fly ash, 21-30 parts of slag, 2-8 parts of hollow microspheres, 17-24 parts of an exciting agent, 3-10 parts of water, 0.8-1.2 parts of a retarder and 1 part of chopped fibers. The preparation method comprises the following steps: adding water into a sodium hydroxide solid to obtain a sodium hydroxide solution; mixing the cooled sodium hydroxide solution with the sodium silicate solution to obtain an exciting agent; the preparation method comprises the following steps: mechanically stirring fly ash, slag and hollow microspheres to obtain a uniformly mixed dry material; adding an exciting agent and water into the uniformly mixed dry material, and uniformly mixing under mechanical stirring to obtain slurry; and adding the chopped fibers into the slurry, and uniformly mixing under mechanical stirring to obtain a final product. The prepared concrete has the advantages of light weight, high strength, high toughness, greenness, low carbon and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials and relates to a light, high-strength and high-toughness green concrete and a preparation method thereof. Background Art

[0002] Traditional cement-based materials are the most widely used building materials in the world. The demand for cement-based materials is increasing rapidly due to infrastructure development and global population growth. However, the production of cement-based materials emits a large amount of greenhouse gases and harmful gases. Therefore, cement must be replaced (partially or completely) with other low-carbon and environmentally friendly materials to maintain sustainable development.

[0003] Compared with ordinary concrete, geopolymers are made from natural aluminosilicate materials (such as metakaolin) or industrial byproducts (such as fly ash and slag) using activators. Due to their lower carbon emissions and energy consumption, geopolymers are considered to be the third generation of concrete cementitious materials for sustainable green building materials after lime and cement. However, alkali-activated cementitious materials have the same disadvantages as cement-based materials, which are prone to cracking and brittle failure.

[0004] In order to limit the defects of brittle failure, the researchers added short fibers to the cementitious material to achieve excellent elongation and tensile strain hardening properties. The tensile strain energy reaches 3% to 10%, which is 300 to 1000 times that of concrete.

[0005] Another direction of concrete material development is lightweight. Structural lightweight aggregate concrete has the dual advantages of reducing deadweight and reducing building energy consumption. The upper limit of structural lightweight aggregate concrete in ACI 213R-14 is 1920kg / m3, and the 28-day compressive strength is 6000psi (40MPa). However, ordinary lightweight aggregates have low strength and poor durability, making it difficult to prepare high-strength and high-performance concrete.

[0006] With the continuous development of the construction industry, a large number of high-rise buildings, long-span bridges and marine projects have emerged, which puts higher requirements on the performance of concrete materials. However, traditional ordinary concrete has problems such as heavy weight (not conducive to earthquake resistance, too large a proportion in reinforced concrete bridges, and does not meet the requirements of offshore oil platforms), low strength, especially low bending and tensile strength (easy to crack and cause incoordination between concrete and steel plates in bridges), poor toughness (not conducive to earthquake resistance), insufficient durability (severe erosion in the marine environment), serious consumption of natural resources and environmental pollution (large amounts of pollution in the cement production process), which restrict its application. Lightweight, high-strength, high-toughness, and green concrete materials will surely become a hot research direction. However, research in this area is still very limited. Summary of the invention

[0007] In order to solve the problems existing in existing concrete materials, the present invention provides a light, high-strength and high-toughness green concrete. Geopolymer is used as a cementitious material to achieve low carbon and environmental protection, hollow microspheres are used as lightweight aggregates to achieve light weight and high strength, and short-cut fibers are added to increase toughness.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] On the one hand, a lightweight, high-strength and high-toughness green concrete is composed of the following raw materials, calculated by weight: 21-30 parts of fly ash, 21-30 parts of slag, 2-8 parts of hollow microspheres, 17-24 parts of activator, 3-10 parts of water, 0.8-1.2 parts of retarder, and 1 part of chopped fiber.

[0010] Preferably, the fly ash is Class F fly ash with (SiO2+Al2O3+Fe2O3)>70%.

[0011] Preferably, the slag is S105 slag with an activity index 28d≥105%.

[0012] Preferably, the hollow microspheres are artificial hollow glass microspheres, the composition of which is Soda lime borosilicate glass and The synthetic amorphous form has a true density of 0.2-0.6 g / cm 3, a particle size of 45-60 μm, and an anti-crushing strength (80% retention) of 3.5-55 MPa.

[0013] Preferably, the activator is an alkaline activator, which is prepared by mixing 2.25 modulus sodium silicate solution and 10 mol / L sodium hydroxide solution in a ratio of 2:1.

[0014] Preferably, the water is tap water.

[0015] Preferably, the retarder is barium chloride with a purity of 96%.

[0016] Preferably, the chopped fibers are ultra-high molecular weight polyvinyl alcohol fibers; and the length of the chopped fibers is 12 mm.

[0017] On the other hand, a method for preparing lightweight, high-strength and high-toughness green concrete comprises the following steps:

[0018] S1. Dissolve solid sodium hydroxide in water, stir rapidly, and then seal with a film to prevent volatilization to obtain a sodium hydroxide solution;

[0019] S2. After the sodium hydroxide solution is cooled, it is mixed with the sodium silicate solution in proportion, and then resealed and cooled for more than 24 hours to obtain an activator;

[0020] S3. The fly ash, slag and hollow microspheres were stirred at a low speed of 75r / min for 3min to obtain a uniformly mixed dry material;

[0021] S4. Add the activator and water to the uniformly mixed dry materials, and stir them thoroughly at a high speed of 135r / min for 2-3min under mechanical stirring until the mixture reaches a flowable state to obtain a slurry;

[0022] S5. Add a small amount of chopped fibers to the slurry continuously and stir the slurry at a high speed of 135 r / min for 5 minutes under mechanical stirring to obtain the final product.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] (1) The present invention uses fly ash and slag as main raw materials to replace cement to prepare cementitious materials, thereby realizing the comprehensive utilization of solid wastes such as fly ash and slag, and greatly reducing the emission of greenhouse gases and harmful gases, which is green and low-carbon.

[0025] (2) The present invention adopts artificial hollow glass microspheres, which have excellent properties such as light weight, high compressive strength, good heat resistance, low thermal conductivity, and good fluidity. Compared with ordinary lightweight aggregates, such as natural aggregates (such as pumice and slag), artificial aggregates (such as expanded clay, expanded shale and fly ash ceramsite) and aggregates recovered from waste (such as palm oil clinker, coconut shells, volcanic slag and industrial waste residue), etc., it is a better raw material for preparing lightweight and high-strength concrete.

[0026] (3) The high elastic modulus and high strength polyethylene fiber used in the present invention can significantly increase the toughness and tensile properties of concrete materials, greatly improve the mechanical properties and crack width of cement-based cementitious composite materials, and improve their durability. The strain rate of the concrete material prepared by the present invention can reach 8.3%, and the tensile strength can reach 7.8MPa.

[0027] (4) The lightweight, high-strength, high-toughness green concrete proposed by the present invention has a density of 1300-1800 kg / m3, a compressive strength of 40-90 MPa, and a density of only 54-75% of that of ordinary concrete.

[0028] (5) The present invention requires fewer types of raw materials, a simple process flow, and a low preparation cost.

[0029] (6) The volume proportion of hollow microspheres in different mix ratios in the present invention has a wide range, from 8.6-36.8%. During the pouring process, the hollow microspheres will absorb water, but the water absorbed by the aggregate cannot be counted as the water in the water-binder ratio. For a constant water-binder ratio, the present invention first determines the saturated surface dry water absorption rate of the hollow microspheres to be 90.2%. Therefore, the total water volume is the water volume in the water-binder ratio plus the water required for the hollow microspheres to reach the saturated surface dry state. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the tensile stress-strain diagram of the lightweight, high-strength and high-toughness green concrete in Example 1;

[0031] Figure 2 It is the tensile stress-strain diagram of the lightweight, high-strength and high-toughness green concrete in Example 2.

[0032] Figure 3 This is the tensile stress-strain diagram of the lightweight, high-strength and high-toughness green concrete in Example 3.

[0033] Figure 4 This is the tensile stress-strain diagram of the lightweight, high-strength and high-toughness green concrete in Example 1.

[0034] Figure 5 This is the tensile stress-strain diagram of lightweight, high-strength and high-toughness green concrete in Example 2 DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The base activator used in the following examples is prepared as follows:

[0037] First weigh the required sodium hydroxide solid, then weigh water at a ratio of 1:2.14, dissolve the sodium hydroxide solid in water, stir quickly, and then seal the beaker mouth with a film to prevent volatilization, and then obtain a 10mol / L sodium hydroxide solution. Then add the sodium hydroxide solution to the sodium silicate solution at a ratio of 1:2, reseal and cool for more than 24 hours, and then obtain the alkali activator for test pouring.

[0038] Example 1

[0039] A light, high-strength and high-toughness green concrete is obtained by the following preparation steps:

[0040] S1. 30.3 parts of fly ash, 30.3 parts of slag, 1.8 parts of hollow microspheres, and 1.2 parts of barium chloride were stirred at a low speed of 75r / min for 3min under mechanical stirring to obtain a uniformly mixed dry material;

[0041] S2. Add 24.2 parts of the activator and 4.6 parts of water to the uniformly mixed dry material, and stir at a high speed of 135r / min for 2-3min under mechanical stirring until the mixture reaches a flowable state to obtain a slurry;

[0042] S3. Add 1 part of chopped fibers in small amounts to the slurry and stir it thoroughly at a high speed of 135 r / min for 5 minutes under mechanical stirring to obtain the final product.

[0043] Example 2

[0044] A light, high-strength and high-toughness green concrete is obtained by the following preparation steps:

[0045] S1. 27.8 parts of fly ash, 27.8 parts of slag, 3.6 parts of 0.4g / cm3 hollow microspheres, and 1.1 parts of barium chloride were stirred at a low speed of 75r / min for 3min under mechanical stirring to obtain a uniformly mixed dry material;

[0046] S2. Add 22.2 parts of the activator and 5.7 parts of water to the uniformly mixed dry material, stir at a high speed of 135r / min for 2-3min under mechanical stirring until the mixture reaches a flowable state to obtain a slurry;

[0047] S3. Add 1 part of chopped fibers in small amounts to the slurry and stir it thoroughly at a high speed of 135 r / min for 5 minutes under mechanical stirring to obtain the final product.

[0048] Example 3

[0049] A light, high-strength and high-toughness green concrete is obtained by the following preparation steps:

[0050] S1. 21 parts of fly ash, 21 parts of slag, 7.6 parts of hollow microspheres, and 0.8 parts of barium chloride were stirred at a low speed of 75r / min for 3min under mechanical stirring to obtain a uniformly mixed dry material;

[0051] S2. 16.8 parts of the activator and 8.7 parts of water were added to the uniformly mixed dry materials, and the mixture was stirred at a high speed of 135 r / min for 2-3 min under mechanical stirring until the mixture reached a flowable state to obtain a slurry;

[0052] S3. Add 1 part of chopped fibers in small amounts to the slurry and stir it thoroughly at a high speed of 135 r / min for 5 minutes under mechanical stirring to obtain the final product.

[0053] Comparative Example 1

[0054] A light, high-strength and high-toughness green concrete is obtained by the following preparation steps:

[0055] S1. 27.8 parts of fly ash, 27.8 parts of slag, 1.7 parts of 0.2g / cm3 hollow microspheres, 1.1 parts of barium chloride were stirred at a low speed of 75r / min for 3min under mechanical stirring to obtain a uniformly mixed dry material;

[0056] S2. Add 22.2 parts of the activator and 4.2 parts of water to the uniformly mixed dry material, and stir at a high speed of 135r / min for 2-3min under mechanical stirring until the mixture reaches a flowable state to obtain a slurry;

[0057] S3. Add 1 part of chopped fibers in small amounts to the slurry and stir it thoroughly at a high speed of 135 r / min for 5 minutes under mechanical stirring to obtain the final product.

[0058] Comparative Example 2

[0059] A light, high-strength and high-toughness green concrete is obtained by the following preparation steps:

[0060] S1. 27.8 parts of fly ash, 27.8 parts of slag, 5 parts of 0.2g / cm3 hollow microspheres, and 1.1 parts of barium chloride were stirred at a low speed of 75r / min for 3min under mechanical stirring to obtain a uniformly mixed dry material;

[0061] S2. Add 22.2 parts of the activator and 7.2 parts of water to the uniformly mixed dry material, and stir at a high speed of 135r / min for 2-3min under mechanical stirring until the mixture reaches a flowable state to obtain a slurry;

[0062] S3. Add 1 part of chopped fibers in small amounts to the slurry and stir it thoroughly at a high speed of 135 r / min for 5 minutes under mechanical stirring to obtain the final product.

[0063] Performance testing

[0064] 1. A testing method for lightweight, high-strength and high-toughness green concrete is provided. The lightweight, high-strength and high-toughness green concrete obtained in Examples 1-3 and Comparative Examples 1-2 is subjected to 28-day compressive strength testing according to standard ASTM C109-16, using a YAW-5000F microcomputer-controlled electro-hydraulic servo pressure testing machine with a loading rate of 1200 N / s.

[0065] 2. A testing method for lightweight, high-strength and high-toughness green concrete is provided. The lightweight, high-strength and high-toughness green concrete obtained in Examples 1-3 and Comparative Examples 1-2 is subjected to a uniaxial tensile performance test according to standard JC / T 2461-2018 and a loading rate of 0.5 mm / min to obtain the tensile strength and tensile strain of the lightweight, high-strength and high-toughness green concrete.

[0066] The test data are shown in Table 1.

[0067]

[0068] Table 1

[0069] Implementation Effect

[0070] It can be seen from Examples 1 to 3 that as the volume percentage of hollow microspheres increases from 8.6% to 36.8%, the density of concrete decreases from 1801kg / m3 to 1359kg / m3, a decrease of 25%. The compressive strength also decreases from 90.10MPa to 40.00MPa, a decrease of 56%. However, according to the provisions of the ACI 213R-14 specification, it still belongs to high-strength concrete. As the volume percentage of hollow microspheres increases from 8.6% to 15.8%, the tensile strength of concrete does not change significantly, all above 7MPa, while the ultimate tensile strain increases by 10%; as the volume percentage of hollow microspheres continues to increase to 36.8%, the tensile strength decreases by 43%, and the ultimate tensile strain decreases by 11%, but still reaches 6.65%.

[0071] It can be seen from Example 1 and Comparative Examples 1 to 2 that the type of hollow microspheres has no significant effect on the tensile and compressive properties of concrete. It is worth noting that at the same volume ratio, the density of concrete using 200kg / m3 microspheres is higher than that using 400kg / m3 microspheres, and the tensile strain is significantly lower than the other two groups. Therefore, it is speculated that the compressive strength of 200kg / m3 microspheres is too low, resulting in breakage during mixing.

[0072] In general, the present invention has a small number of raw material types and a simple process flow, and the prepared concrete has the advantages of light weight, high strength, high toughness, and being green and low-carbon.

[0073] Although the above embodiments have been described in detail for the present invention, it should be understood by those skilled in the art that modifications or improvements may be made based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention, and such modifications and improvements are within the spirit and scope of the present invention.

Claims

1. A light, high-strength and high-toughness green concrete, characterized in that: The invention comprises the following components: 21-30 parts of fly ash, 21-30 parts of slag, 2-8 parts of hollow microspheres, 17-24 parts of activator, 3-10 parts of water, 0.8-1.2 parts of retarder and 1 part of short-cut fiber.

2. A lightweight, high-strength, high-toughness green concrete according to claim 1, characterized in that: The fly ash is Class F fly ash with (SiO2+Al2O3+Fe2O3)>70%; the slag is S105 slag with an activity index of 28d≥105%.

3. The light, high-strength, high-toughness green concrete according to claim 1, characterized in that: The hollow microspheres are artificial hollow glass microspheres, and the composition is Soda lime borosilicate glass and The synthetic amorphous form has a true density of 0.2-0.6 g / cm 3, a particle size of 45-60 μm, and an anti-crushing strength (80% retention) of 3.5-55 MPa.

4. The light-weight, high-strength, high-toughness green concrete according to claim 1, characterized in that: The activator is an alkali activator, which is mainly prepared by mixing a 2.25 modulus sodium silicate solution and a 10 mol / L sodium hydroxide solution in a ratio of 2:

1.

5. The light, high-strength, high-toughness green concrete according to claim 1, characterized in that: The retarder is barium chloride.

6. The light, high-strength, high-toughness green concrete according to claim 1, characterized in that: The chopped fibers are ultra-high molecular weight polyvinyl alcohol fibers; the length of the chopped fibers is 12 mm.

7. The method for preparing a lightweight, high-strength, high-toughness green concrete according to claim 1, characterized in that: The following steps are involved: S1. Dissolve solid sodium hydroxide in water, stir rapidly, and then seal with a film to prevent volatilization to obtain a sodium hydroxide solution; S2. After the sodium hydroxide solution is cooled, it is mixed with the sodium silicate solution in proportion, and then resealed and cooled for more than 24 hours to obtain an activator; S3. The fly ash, slag, and hollow microspheres are fully stirred at a low speed of 75r / min for 3 minutes under mechanical stirring to obtain a uniformly mixed dry material; S4. Add the activator and water to the uniformly mixed dry materials, stir them thoroughly at a high speed of 135 r / min for 2-3 minutes under mechanical stirring, until the mixture reaches a flowable state to obtain a slurry; S5. Add a small amount of chopped fibers to the slurry continuously, stir them thoroughly at a high speed of 135 r / min for 5 minutes under mechanical stirring, and mix them uniformly to obtain the final product.